Pramipexole is active in depression tests and modulates monoaminergic transmission, but not brain levels of BDNF in mice - Schulte-Herbrüggen, Olaf; Vogt, Miriam A.; Gass, Peter (European journal of pharmacology, 2011)
The dopamine D2/D3 receptor agonist pramipexole exerts antidepressive capacities in patients with Parkinson's disease with little evidence for patients with affective diseases only. Little is known about the neurobiological basis of these antidepressive effects. In this study, C57BL/6N mice received acute or chronic (3weeks) treatment with pramipexole in different dosages (0.1, 0.3, 1, and 3mg/kg b.w.) and imipramine or saline serving as positive and negative controls. To characterize antidepressant-like effects mice underwent behavioral characterization. In a second experiment dosages of pramipexole shown to be effective were used and candidate brain regions including hippocampus, frontal cortex and striatum were analyzed for levels of 5-hydroxytryptamine (5-HT), noradrenaline and dopamine and their metabolites as well as brain-derived neurotrophic factor (BDNF) to investigate possible neurochemical correlates of behavioral changes. Whereas acute treatment with pramipexole resulted in antidepressive-like effects in the Porsolt Forced Swim Test, Novel Cage Test, Openfield Test and Dark-light-Box Test and a tendency but insignificant effect in the Tail Suspension Test, chronic treatment did not show significant effects in any of the behavioral analyses. Neurochemical analyses revealed a highly significant effect on dopaminergic metabolites in the striatum as well as a moderate transient modulation of the serotonergic system in the hippocampus. BDNF levels were not affected by any dosage and treatment regime in any brain region investigated. In conclusion, the present data substantiate antidepressive effects of pramipexole and indicate a contribution of the dopaminergic and serotonergic metabolism in these effects, but argue against an eminent role of BDNF.